Odpowiedzi

2009-09-21T22:04:33+02:00
Dla
A=(x₁, y₁)
B=(x₂, y₂)
Prosta przechodząca przez punkty to
y - y₁ = (y₂-y₁)/(x₂-x₁) * (x - x₁)

Przemnażasz, przerzucasz y₁ na drugą stronę i masz odpowiedź.
2009-09-21T22:23:15+02:00
A) y = 5,5x - 4
b) y = x + 3
c) y = 3/10x + 1/2
d) y = -5/4x
e) y = -5x
Najlepsza Odpowiedź!
2009-09-21T22:59:16+02:00
A) (0,-4) i (2,7)
b=-4
y=ax-4
7=2a-4
2a=11
a=5,5
y=5,5x-4

b) (0,3) i (-1,2)
b=3
y=ax+3
2=-1a+3
a=1
y=x+3

c) (0,1/2) i (-5,-1)
b=1/2
y=ax+1/2
-1=-5x+1/2
5a=1 1/2
a=0,3
y=0,3x+1/2

d) (0,0) i (-4,5)
b=0
y=ax
5=-4a
a=-5/4
t=-5/4

e) (0,0) i (-2,10)
b=0
y=ax
10=-2a
a=-5
y=-5x